A simulation-based approach for evaluating diverse inventory policies in a supply chain. (6th October 2008) - Xudong, Xie; Kumar, Arun; Tan, Albert Wee Kwan
Most of the current literature in supply chain inventory management focuses solely on series systems in which the analytical models become too complicated to be solved when considering various inventory policies concurrently. The authors present a new simulation-based approach to evaluate the inventory policies in a supply chain that analyses continuous and periodic review policies. Further, this paper proposes a combined performance measure, which considers total supply chain cost and customer service level using a case study. Based on the design of experiment, comparison is made on the impact of different configuration of inventory policies upon the combined performance measurement.